A manutenção do equilíbrio econômico de contratos de obras públicas empreitadas: parâmetros para o estudo de riscos vinculados a atrasos no encaixe do preço - MATTOS, Renato Marinho Meira (2004)
In the Civil Engineering field, one of the most important segments is the global piecework, the one that is made by an agreement and by the right and total price. Public works, that are meant to attend a public utility, and whose contracts are ruled by the 8.666/93 Law, are often bided this way. Article 58 of this Law determines that the economic-financial balance of these contracts must be kept. The theoric fundamentation concerns of public works concepts, the most important aspects of 8.666/93 Law, economic-financial analysis and risks analysis. This paper presents, also, a systematic and numeric simulation to piecework undertaking im Civil Engineering field. The goal of this paper is to create parameters for the establishment of protection margins for due-date extension, and respective price receiving, as determined by 8.666/93 Law, thus keeping the original balance. Based on 63 analyzed construction works, the economic-financial balance is verified, comparing the expected restricted return rate at the bidding moment, with the one that was actually obtained in the operation. From the deviation detected in the return rates between those two different moments, parameters for covering the referred risks are created by a simulation process and sensibility analysis. First, at the bidding moment, the restrict return mean rate is 9,45% a month. At the second moment, this rate falls to 5,16% a month. It represents, in mean, 45,39% of variation. The atractive mean rate based on the analysed public construction works is between 6% to 13% a month. The calculated parameters for due-date extension and respective price receiving is between 1,5% to 11,5% of price. Therefore, in the analysed public works, dont exist the economic-finacial maintaining balance.